MICROBIOLOGICAL QUALITY ASSESSMENT OF BEACH SAND IN MOSTAGANEM (SIDI MEJDOUB AS CASE STUDY). - Cobbinah, Justina Attaa Panyin (My University, 2023)
Sandy beaches are popular recreational destinations where beachgoers spend much of their time rather than in the water. Mediterranean areas, such as beaches, play an important role in human recreation; nevertheless, they expose humans to pathogenic bacteria and microorganisms directly or indirectly through anthropogenic activities resulting in pollution. The objective of this study was to assess the microbiological quality of Sidi Majdoub beach sand in Mostaganem (Algeria). The studied sand samples were taken from three different sites on this beach and then their microbiological quality was examined to detect the presence of contamination indicator microorganisms by isolating, identifying them by macroscopic and microscopic observation and performing some biochemical tests. . The results obtained indicate that the 3 sites have mediocre microbiological quality due to the presence of indicator microorganisms such as Staphylococcus spp., Pseudomonas spp., Enterobacteria, Penicillium spp., yeast (candida) and Cladosporium. The results indicate also that among the three sites studied, the site C was found to have the highest microbial density and Staphylococcus spp. was the most dominant bacteria detected. In this study Enterobacteriaceae and Pseudomonas were resistant to beta-lactam antibiotics such as Piperacillin, amoxicillin and clavulanic acid.
Keywords: Microbiological quality; Sand beaches; bacteria; fungi; antibiotics